Pursuing reliable thermal analysis techniques for energetic materials: decomposition kinetics and thermal stability of dihydroxylammonium 5, 5′-bistetrazole-1, 1′-diolate (TKX-50). Issue 1 (1st December 2016) - Muravyev, Nikita V.; Monogarov, Konstantin A.; Asachenko, Andrey F.; Nechaev, Mikhail S.; Ananyev, Ivan V.; Fomenkov, Igor V.; Kiselev, Vitaly G.; Pivkina, Alla N.
Abstract : Reliable kinetics of thermolysis for a novel explosive dihydroxylammonium 5, 5′-bistetrazole-1, 1′-diolate (TKX-50 ) was obtained using a variety of thermoanalytical and kinetic methods and verified by modeling of adiabatic self-heating. Abstract : Thermal decomposition of a novel promising high-performance explosive dihydroxylammonium 5, 5′-bistetrazole-1, 1′-diolate (TKX-50 ) was studied using a number of thermal analysis techniques (thermogravimetry, differential scanning calorimetry, and accelerating rate calorimetry, ARC). To obtain more comprehensive insight into the kinetics and mechanism ofTKX-50 decomposition, a variety of complementary thermoanalytical experiments were performed under various conditions. Non-isothermal and isothermal kinetics were obtained at both atmospheric and low (up to 0.3 Torr) pressures. The gas products of thermolysis were detected in situ using IR spectroscopy, and the structure of solid-state decomposition products was determined by X-ray diffraction and scanning electron microscopy. Diammonium 5, 5′-bistetrazole-1, 1′-diolate (ABTOX ) was directly identified to be the most important intermediate of the decomposition process. The important role of bistetrazole diol (BTO ) in the mechanism ofTKX-50 decomposition was also rationalized by thermolysis experiments with mixtures ofTKX-50 andBTO . Several widely used thermoanalytical data processing techniques (Kissinger, isoconversional, formal kinetic approaches, etc. ) were independently benchmarked against the ARC data, which are more germane to the real storage and application conditions of energetic materials. Our study revealed that none of the Arrhenius parameters reported before can properly describe the complex two-stage decomposition process ofTKX-50 . In contrast, we showed the superior performance of the isoconversional methods combined with isothermal measurements, which yielded the most reliable kinetic parameters ofTKX-50 thermolysis. In contrast with the existing reports, the thermal stability ofTKX-50 was determined in the ARC experiments to be lower than that of hexogen, but close to that of hexanitrohexaazaisowurtzitane (CL-20).